2020
DOI: 10.34234/ded.736639
|View full text |Cite
|
Sign up to set email alerts
|

Eğitsel Oyunların Öğrencilerin Değer Kazanımlarına Etkisi: Bir Durum Çalışması

Abstract: Bu makale, en az iki hakem tarafından incelendi ve intihal içermediği teyit edildi. / This article has been reviewed by at least two referees and scanned via a plagiarism software. ded Öz: Bu araştırmanın temel amacı ilkokul öğretim programlarında yer alan adalet, dostluk, dürüstlük, sabır, sorumluluk, dayanışma, eşitlik değerleri kapsamında tasarlanan ve ders kazanımları ile doğrudan ilişkilendirilen eğitsel oyunların öğrencilerin bilişsel yapılarına etkisi ve öğretmen görüşlerine göre incelenmesidir. Nitel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…They found that games developed values in students. Izgar (2020) stated that educational games prepared to teach values (honesty, friendship, responsibility, patience, equality, solidarity, justice) positively affect students' cognition levels. Gündüz, Aktepe et al (2017) stated that values can be acquired at an early age through educational games in their research on preschool students.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that games developed values in students. Izgar (2020) stated that educational games prepared to teach values (honesty, friendship, responsibility, patience, equality, solidarity, justice) positively affect students' cognition levels. Gündüz, Aktepe et al (2017) stated that values can be acquired at an early age through educational games in their research on preschool students.…”
Section: Resultsmentioning
confidence: 99%
“…Literatürdeki çalışmalara benzer şekilde (Bozkurt, 2017;Biter ve Çalışkan, 2019;Gündüz, Aktepe, Uzunoğlu ve Gündüz, 2017;Izgar, 2020) bu çalışmada da eğitsel oyunlarla yürütülen eğitimin değerlerle ilgili öğrencilerde farkındalık yarattığı tespit edilmiştir.…”
Section: Discussionunclassified
See 3 more Smart Citations